Dampak Kebijakan Perluasan Ganjil Genap Terhadap Jumlah Penumpang dan Pendapatan Transjakarta - Erni Pratiwi Perwitasari; Tri Mulyani Setyowati; Sri Handayani (Institut Transportasi dan Logistik Trisakti, 2021)
The DKI Jakarta Government has carried out evaluations and established regulations related to congestion that occurs in DKI Jakarta as the capital of the Republic of Indonesia. The Government's efforts in overcoming the congestion that occurred were that the 3 in 1 (three in one) program was established and implemented which was later replaced by the odd-even regulation on certain roads in the capital area. In 2018 odd-even trials were carried out during the Asian Games, until September 9, 2019, the DKI Jakarta Provincial Government determined an expansion of the odd-even area as an effort to stop the congestion that occurred. The purpose of this study is to determine and analyze dThe effect of the odd-even expansion policy on the number of passengers and revenue of TransJakarta in 2019 using path analysis. The calculation is done using Eviews 10 software with panel data type, namely a combination of cross section data with time series. This study uses secondary data regarding the number of TransJakarta passengers and TransJakarta revenue from corridors 1 towith 13 in 2019 that have been published. The choice of model in this study is the Random Effect Model which results in the findings of the research, namely that there is a significant direct or indirect effect between the Odd-Even Expansion Policy on TransJakarta Income through the Number of Passengers.